Cambodian and Thai Political Actors Interest in Preah Vihear Temple Border Conflict in 2008-2011 - Putri, Indah Merdeka; Muhyidin, Ali (Jurnal Politik, 2019)
This paper examines how domestic interest of political actors in particular country may spark conflict and create reconciliation with other country. The case of the Preah Vihear border temple dispute between Cambodia and Thailand in 2008-2011 shows that distinctive political interest within each country has made the the relation of both countries in up and down situation, in term of escalating conflict or initiating reconciliation, in that period of time. By discussing the interest of Cambodia’s political actor represented by Prime Minister Hun Sen with the Cambodian’s People Party (CPP) and Thailand’s elites represented by Prime Minister Abhisit Vejjajiva with the Democracy Party (PD) and, later, by Yingluck Shinawatra with the Pheu Thai Party, the article argues that Preah Vihear conflict has been used by these political actors for their domestic political gains. Based on this study, it can be concluded that a border conflict can be basically influenced by political actor interest to maintain or gain domestic power. By underlining the domestic political actor interest, this study gives a different dimension compare to other studies at the same topic that tend to explain the conflict by using descriptive or chronolical approach.